2017
DOI: 10.1186/s12936-017-1874-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of climate-driven variations in malaria incidence in Swaziland: toward malaria elimination

Abstract: BackgroundSwaziland aims to eliminate malaria by 2020. However, imported cases from neighbouring endemic countries continue to sustain local parasite reservoirs and initiate transmission. As certain weather and climatic conditions may trigger or intensify malaria outbreaks, identification of areas prone to these conditions may aid decision-makers in deploying targeted malaria interventions more effectively.MethodsMalaria case-surveillance data for Swaziland were provided by Swaziland’s National Malaria Control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 41 publications
(48 reference statements)
2
12
0
Order By: Relevance
“…The study in the relationship between humidity and dengue have received less attention, and humidity is likely influencing on vector competence under the interaction with temperatures but not alone [ 57 ]. The positive association between temperature and malaria observed in this study was also reported from previous studies [ 58 , 59 ]. However, the negative relationship between rainfall and malaria found in this study is inconsistent with that observed in the previous study.…”
Section: Discussionsupporting
confidence: 92%
“…The study in the relationship between humidity and dengue have received less attention, and humidity is likely influencing on vector competence under the interaction with temperatures but not alone [ 57 ]. The positive association between temperature and malaria observed in this study was also reported from previous studies [ 58 , 59 ]. However, the negative relationship between rainfall and malaria found in this study is inconsistent with that observed in the previous study.…”
Section: Discussionsupporting
confidence: 92%
“…The month lagged effects of temperature would avail time long enough to design interventions to interrupt malaria transmission, despite temperature values used in the current study being high as compared to the optimal temperature for malaria transmission of 29 o C [35]. However, this nding was consistent with previous studies which have demonstrated how temporal disease risk shifts in response to temperature changes and increase in maximum temperature increases the incidence rate of malaria signi cantly of the current month and later [36][37][38].…”
Section: Discussionsupporting
confidence: 88%
“…The data will also provide a valuable input to modelling efforts to understand the effects of individual-level characteristics and spatial importation risk, e.g., where imported cases most often appear and their likelihood of prompting onward transmission to refine existing estimates and risk maps [ 18 , 33 ]. The data could also prove useful in parameterizing models of human and parasite mobility that can be extended beyond Swaziland, as well as compared to other forms of mobility data, such as from mobile phones [ 7 ], census microdata [ 33 , 34 ] or parasite genotyping [ 35 ] and, to strengthen assessments of the impact of climatic variations and incidence on malaria transmission [ 36 ] or genetic studies that further the understanding of transmission dynamic in low transmission settings [ 18 ].…”
Section: Discussionmentioning
confidence: 99%